Nanotoxicity: A Growing Need for Study in the Endocrine System. Issue 9 (11th February 2013) - Lu, Xuefei; Liu, Ying; Kong, Xiangjun; Lobie, Peter E.; Chen, Chunying; Zhu, Tao
Abstract Nanomaterials (NMs) are engineered for commercial purposes such as semiconductors, building materials, cosmetics, and drug carriers, while natural nanoparticles (NPs) already exist in the environment. Due to their unique physicochemical properties, they may interact actively with biological systems. Some of these interactions might be detrimental to human health, and therefore studies on the potential 'nanotoxicity' of these materials in different organ systems are warranted. The purpose of developing the concept of nanotoxicity is to recognize and evaluate the hazards and risks of NMs and evaluate safety. This review will summarize and discuss recent reports derived from cell lines or animal models concerning the effects of NMs on, and their application in, the endocrine system of mammalian and other species. It will present an update on current studies of the effects of some typical NMs—such as metal‐based NMs, carbon‐based NMs, and dendrimers—on endocrine functions, in which some effects are adverse or unwanted and others are favorable or intended. Disruption of endocrine function is associated with adverse health outcomes including reproductive failure, metabolic syndrome, and some types of cancer. Further investigations are therefore required to obtain a thorough understanding of any potential risk of pathological endocrine disruption from products containing NMs. This review aims to provide impetus for further studies on the interactions of NMs with endocrine functions.